Grenada. Significant achievements 2010 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Granada during 2010 are identified, with respect to the needs and interests of the country, strengthening issues such as agribusiness, waste management, training, financing, technical support, leadership, composting, production, technology, organic farming, food processing, greenhouses, and composting.